The force-velocity profiling concept for sprint running is a dead end - Ettema, G. (International Journal of Sports Physiology and Performance, 2024)
Purpose: In this commentary, I present arguments against the use of the force-velocity profiling concept in design and adaptations of training programs targeting sprinting. The purpose of this commentary is to make sports practitioners more aware of the rationale behind the concept and explain why it does not work.